Searching For Management Solutions in Fulfillment of Receipt Target Parking Taxes and Levies in Medan City - Yuswar Effendy (INSPIRETECH GLOBAL INSIGHT, 2026)
The application of the concept of decentralized and regional autonomy in Indonesia, especially in Medan City, is still not available to show maximum results as expected, especially regarding potential revenue. One of these revenues to the local government that is potential is about parking. Still found some flaws in the application of its management, including the fulfillment of tax revenue targets and parking fees in the city of Medan. With the fulfillment of tax revenue targets and parking fees, the city of Medan will be able to increase the independence of the region through increased regional tax revenue. Tax effort is to increase the local tax measured by the ratio between the actual source of revenue to a source of potential revenue. It takes qualified human resources and management oversight that maximum parking tax in Medan can contribute the maximum so as to meet the target of tax revenue and levies to support the budget.